Work-Family Conflict, Job Satisfaction and Burnout in Nurses: A Correlational Study in Punjab (Pakistan) (Journal of Asian Development Studies, 2025)
This research investigates the relationship between work-family conflict (WFC), job satisfaction (JS), and burnout among female nurses working in public and private hospitals in Punjab, Pakistan. Nursing is a profession characterised by long working hours, emotional labour, and high responsibility for patient care. In Pakistani culture, women are expected to manage family caregiving alongside employment, creating a double burden. This study applies Role Conflict Theory, Boundary Theory, and the Conservation of Resources model to explain how work-family conflict impacts job satisfaction and burnout. A sample of 300 nurses aged 25–60 years participated in the study, using standardised scales: the Work-Family Conflict Scale (Haslam et al., 2015), Job Satisfaction Survey (Spector, 1994), and Maslach Burnout Inventory (Maslach, 1981). Data analysis included descriptive statistics, correlation analysis, and regression analysis. Results showed that WFC positively predicted burnout and negatively predicted job satisfaction. Findings highlight the urgent need for flexible scheduling, supportive leadership, and family friendly policies in healthcare institutions to mitigate burnout. This study makes a novel contribution by exploring WFC, job satisfaction, and burnout together in Pakistan's nursing sector, offering valuable insights for healthcare management and policymakers.